Literature Review: Perubahan Bone Mineral Density pada Pasien Osteoporosis setelah Pemberian Risedronate - Chantia Ningrum; Meldy Muzada Elfa; Lena Rosida (Homeostasis, 2021)
Abstract: Bone mineral density (BMD) in osteoporosis can be maintained by inhibiting osteoclast activity and stimulating apoptosis by administering risedronate. Risedronate is an antiresorptive agent for prevention and treatment of osteoporosis. Writing this literature review aims to summarize changes in BMD in osteoporosis patients after administration of risedronate. Writing is done by analyzing the literature related to the search results databases of medical journals, namely PubMed – MEDLINE and Google Scholar. Articles included in English and Indonesian and published in 2010-2020. There are 17 articles used in this literature review. Risedronate can increase changes in BMD in some parts of the bone, but there are also parts of the bone that have decreased BMD. The difference in changes in other bone sites is influenced by patient characteristics in treatment adherence. Further research is needed to determine changes in BMD in osteoporosis patients after administration of the risedronate. Keywords: risedronate, bone mineral density, osteoporosis, therapy Abstrak: Bone mineral density (BMD) pada osteoporosis dapat dipertahankan dengan cara menghambat aktivitas osteoklas dan memacu apoptosis dengan pemberian risedronate. Risedronate adalah salah satu agen antiresorptive sebagai pencegahan dan pengobatan osteoporosis. Penulisan literature review ini bertujuan untuk merangkum perubahan BMD pada pasien osteoporosis setelah pemberian risedronate. Penulisan dilakukan dengan menganalisis literature terkait yang didapatkan dari hasil pencarian database jurnal kedokteran, yaitu PubMed–MEDLINE dan Google Scholar. Artikel yang disertakan menggunakan Bahasa Inggris dan Bahasa Indonesia serta dipublikasikan pada tahun 2010-2020. Sebanyak 17 artikel disertakan pada literature review ini. Risedronate dapat meningkatkan perubahan BMD di beberapa bagian tulang, namun ada juga bagian tulang yang mengalami penurunan BMD. Perbedaan perubahan pada bagian-bagian tulang lainnya dipengaruhi dari karakteristik pasien dalam kepatuhan berobat. Penelitian lebih lanjut diperlukan untuk mengetahui perubahan BMD pada pasien osteoporosis setelah pemberian risedronate tersebut. Kata-kata kunci: risedronate, densitas mineral tulang, osteoporosis, terapi